Association of Thrombotic Microangiopathy and Intimal Hyperplasia With Bleeding Post–Renal Biopsy in Antiphospholipid Antibody–Positive Patients. Issue 5 (May 2014) - Jordan, Natasha; Chaib, Ahlem; Sangle, Shirish; Tungekar, Fahim; Sabharwal, Tarun; Abbs, Ian; Khamashta, Munther; D'Cruz, David
<x xml:space="preserve">Abstract</x> Objective Renal biopsy remains the gold standard investigation for both diagnostic and prognostic purposes in the clinical management of lupus nephritis. However, it is not without potentially significant complications. The objectives of this study were to determine the rate of significant bleeding post–renal biopsy in patients with lupus nephritis and to identify risk factors associated with hemorrhagic complications. Methods Clinical data were retrospectively collected on 215 renal biopsies performed over a 13‐year period (1999–2012). Patients were categorized into 3 groups: a diagnosis of systemic lupus erythematosus (SLE) alone, SLE with coexisting antiphospholipid syndrome (APS), or a diagnosis of SLE with either positive anticardiolipin antibodies and/or lupus anticoagulant (LAC) without clinical APS manifestations. Results Major bleeding complications were significantly more common in those with coexisting APS and/or antiphospholipid antibodies (aPL). LAC, presence of thrombotic microangiopathy (TMA) on renal biopsy, older age at the time of the biopsy (age >40 years), and elevated serum creatinine (>400 μmoles/liter) were independent risk factors for increased risk of bleeding. TMA and severe fibrous intimal hyperplasia on renal biopsy were significantly more prevalent in those who developed severe bleeding complications. Conclusion Based on these findings, lupus nephritis patients with coexisting APS, positive LAC, and histologic evidence of TMA and/or fibrous intimal hyperplasia are at increased risk of bleeding post–renal biopsy. aPL should be checked in all lupus nephritis patients before undergoing renal biopsy, as this subset of patients warrants particular caution pre‐ and postprocedure.